Endocervix exhibits greater susceptibility to HIV-1 infection compared to ectocervix following ex vivo exposure to Transmitted/Founder HIV-1 variants - Robert Langat; Michael D. McRaven; Ramon Lorenzo-Redondo; Teresia Muhomah; Ann M. Carias; Muhammad Shoaib Arif; Matrona Mbendo Akiso; Marianne Mureithi; Omu Anzala; Jill Gilmour; Sarah Joseph; Thomas J. Hope (PLoS ONE, 2025)
The kinetics and identification of targets of Human Immunodeficiency Virus (HIV) infection within mucosae is a valuable tool for the development of new HIV-prevention strategies. Human tissue explants offer an informative model for studying HIV-1 pathogenesis and can support the development of novel HIV prevention interventions. Here, we infected cervical explants from HIV-1-uninfected women undergoing routine surgery with HIV BaL , a lab-adapted virus, and isolates HIV 4790 and HIV 4791 , transmitted/founder (T/F) HIV-1 variants, and monitored the subsequent viral infection and replication using real-time quantitative PCR. The rates of infection and replication of HIV-1 BaL exceeded those of both HIV 4790 and HIV 4791 . The two T/F isolates were not significantly different from each other overall in the explant comparison (endo and ecto cervical tissue combined); however, all three viruses demonstrated different tissue tropism. HIV-1 BaL and HIV 4790 replicated at equivalent levels in endocervical explants, but HIV 4790 replicated significantly less well in ectocervical explants. Alternatively, HIV 4791 demonstrated inferior replication in endocervical tissues compared to HIV BaL and HIV 4790 but improved replication in ectocervical explants compared to HIV 4790 . Immunofluorescent analysis of the cervical tissues revealed the presence of viable immune cells that are targets of HIV-1 infection, thus validating our ex vivo model in its ability to maintain viable cells in culture for a longer period. This allows for assessing the dynamics of HIV replication in the cervical tissues. Our data suggests that endocervical tissues may be more susceptible to HIV-1 infections than ectocervix, revealing the complex dynamics across different sites of the lower female reproductive tract.